Making Decisions Better: an evaluation of an educational intervention. Issue 2 (31st May 2016) - Thomson, Carrie Louise; Maskrey, Neal; Vlaev, Ivo
Abstract: Rationale, aims and objectives: Despite the widespread inclusion of consultation skills in undergraduate healthcare curricula, patient–doctor interactions are often an imparting of evidence or information rather than an exchange . Evidence‐based practice may be further enhanced by increasing explicit understanding of decision‐making processes used by healthcare professionals and patients. This exploratory investigation evaluated the impact of an educational intervention on understanding of decision‐making processes and practice. The effect of session schedule was assessed to inform the future delivery strategy of such approaches. Methods: Three groups of primary care health professionals ( n  = 85) completed questionnaires using Likert scales to assess strength of agreement with decision‐making statements exploring four themes – Theory, Applied Theory, Practice and Joint Practice – pre‐intervention and post‐intervention. Responses were analysed, firstly to assess the impact of the intervention on understanding of decision‐making processes and practice across all participants and then by group to determine the effect of session schedules on outcome measures. Results: Overall agreement with the decision‐making statements significantly increased after the learning set ( Mean  = −0.162, SD  = 0.355); t (64) = −3.666, p  < 0.001). Multivariate analysis on effect of session schedule only found significant interactions for the theme 'Joint Practice' with group ( p  < 0.025) and 3‐way interaction of Group and Main role. ( p  < 0.048). No consistent positive impact of longer session schedule was found. Conclusion: Participation in the learning sessions significantly improved self‐reported understanding of decision‐making processes and application to clinical practice. The extended learning sessions did not provide additional benefits over and above 2 half days or 1 whole day learning sessions.